The value of cytology in diagnosis of serous effusions in malignant lymphomas: An experience of a tertiary care center. Issue 8 (15th May 2019) - Patel, Trupti; Patel, Priya; Mehta, Shailee; Shah, Majal; Jetly, Dhaval; Khanna, Nisha
Abstract: Background: Malignant lymphomas (ML) are often complicated by serous effusions. The present study is an attempt to cytologically assess a large series of serous effusions associated with ML, identify the immunoreactivity of cells and to evaluate the role of various ancillary methods in confirming and subtyping these cases. Methods: A cross‐sectional study of 4612 serous effusions was undertaken at the Department of Cytology, Gujarat Cancer and Research Institute by retrieving data from the year 2015 to 2017. Total 169 cases of ML, clinically suspicious, were included. All cerebrospinal fluids, serous effusions involved by myeloid neoplasms, and cases of primary effusion lymphomas were excluded from our study. Pap stained smears of all these serous effusions were examined. Ancillary methods such as immunohistochemistry were used to further subtype the positive cases using the WHO classification of hematopoietic and lymphoid neoplasms (2016). Results: Out of total 169 clinically suspicious cases, 109 cases were cytologically positive for ML which included 73 (66.9%) pleural effusions, 34 (31.1%) ascitic fluids, and 2 (1.8%) pericardial effusions. T‐lymphoblastic lymphoma (36.9%) and Burkitt's lymphoma (38.2%) were the most common ML involving the pleural and ascitic fluids respectively. Non‐Hodgkin's lymphoma (NHL) more frequently involved the serous cavities than Hodgkin's lymphoma. ( P value <.0001). Among the NHL, T‐cell lymphomas more commonly lead to serous effusions than B‐cell lymphomas ( P value <.0048). Conclusion: Cytological examination of serous effusions is an accurate, prompt, affordable technique having diagnostic and therapeutic implications. With the help of ancillary methods, we can identify the phenotype of cells, classify as well as confirm our diagnosis.